Three new species of Dicranopygium (Cyclanthaceae) from Colombia - Álvarez-Correa, Catalina M.; Sanín, David; Alvarez-B, Camilo; Tuberquia, Dino (Phytotaxa, 2026)
Three new species are described of the genus Dicranopygium: D. elongatum, D. piedemontanum, and D. rio-clarense, distributed in Colombia. D. elongatum and D. rio-clarense are presented in lowlands of Antioquia department and D. piedemontanum prosper in the Andean-Amazon foothill from Caquetá and Cauca departments. They are comparing with the morphologically similarities and useful characters are provided for their taxonomic determination. Additionally, a map of their distribution is included and diagnostic images.